The Nuclear Receptor Corepressor (NCoR) Controls Thyroid Hormone Sensitivity and the Set Point of the Hypothalamic-Pituitary-Thyroid Axis - Astapova, Inna (Endocrine Society, 2011)
The role of nuclear receptor corepressor (NCoR) in thyroid hormone (TH) action has been difficult to discern because global deletion of NCoR is embryonic lethal. To circumvent this, we developed mice that globally express a modified NCoR protein (NCoRΔID) that cannot be recruited to the thyroid hormone receptor (TR). These mice present with low serum T(4) and T(3) concentrations accompanied by normal TSH levels, suggesting central hypothyroidism. However, they grow normally and have increased energy expenditure and normal or elevated TR-target gene expression across multiple tissues, which is not consistent with hypothyroidism. Although these findings imply an increased peripheral sensitivity to TH, the hypothalamic-pituitary-thyroid axis is not more sensitive to acute changes in TH concentrations but appears to be reset to recognize the reduced TH levels as normal. Furthermore, the thyroid gland itself, although normal in size, has reduced levels of nonthyroglobulin-bound T(4) and T(3) and demonstrates decreased responsiveness to TSH. Thus, the TR-NCoR interaction controls systemic TH sensitivity as well as the set point at all levels of the hypothalamic-pituitary-thyroid axis. These findings suggest that NCoR levels could alter cell-specific TH action that would not be reflected by the serum TSH.